APPLICATION OF PROJECT BASED LEARNING BASED OF WORKSHEET TO STUDENT’S CRITICAL THINKING SKILLS - Yenni Dwi Aprilita Sagala; Mariati P. Simanjuntak; Nurdin Bukit; Motlan Motlan (Jurnal Pendidikan Fisika, 2019)
Project based learning model (PjBL) is a model that is designed to train students to make plans and produce products that can solve problems in the surrounding environment. The PjBL model has five phases, there are (1) finding ideas, (2) designing the project, (3) compiling the project, (4) implementing the project, and (5) evaluating the project. The purpose of this study is to determine students ‘critical thinking skills and improve student’s critical thinking skills in learning physics through the PjBL model. The design in this study used one group pre-test post-test design on 60 students in Senior High School State of 12 Medan (SMA Negeri 12 Medan) at academic year 2019/2020. The instrument of students’ critical thinking skills uses 7 essay tests using indicators by Ennis, namely: (1) elementary clarification, (2) basic support, (3) inferring, (4) advanced clarification, and (5) strategy and tactic. Analysis of the data used is N-gain. The results of this study are students’ critical thinking skills in the medium category. And the improvement of students’ critical thinking skills is also in the medium category